Experimental investigation on strain behavior of jute/polyester composite with an open hole under axial loading - Anggit Murdani; Utsman Syah Amrullah; R.N. Akhsanu Takwim (Politeknik Negeri Lhokseumawe, 2023)
Mechanical assembly requires joint mechanism involving fasteners and holes. Deformation of the holes will greatly affect the integrity of the mechanical joins. This research objective is to reveal the strain behavior of jute/polyester composite containing open hole under axial loading. It is very important to know the behavior of the strain surrounding the hole under loading. Experiments were carried out by preparing jute/polyester composites. The composites were manufactured by using a vacuum infusion method. There are two configurations of the number of laminations, i.e., 3 and 5 sheets and of hole sizes, i.e., 5 and 10mm holes. An axial load is applied to the specimen through a tensile test. Strain gauges are attached near the holes, axially and laterally. Strain in axial and lateral directions in the vicinity of a hole is recorded and presented. The research result shows that the strain gauges located parallel to the loading axis indicate a positivestrain value. On the other hand, the strain gauges located lateral to the loading axis indicate a negative value. Furthermore, the strain gauges located beside the hole in the direction parallel to the loading axis indicate the highest strain value in all types of specimens.